Inside the Developing Brain to Understand Teen Behavior From Rat Models: Metabolic, Structural, and Functional-Connectivity Alterations Among Limbic Structures Across Three Pre-adolescent Stages - Zoratto, Francesca; Altabella, Luisa; Tistarelli, Naomi; Laviola, Giovanni; Adriani, Walter; Canese, Rossella (Frontiers in Behavioral Neuroscience, 2018)
Adolescence is an age of transition where most brain structures undergo drastic modification, become progressively more interconnected and also undergo several changes from a metabolic and structural viewpoint. In the present study, rs-fMRI is used in a rat model to investigate how these patterns of connectivity change , in particular for what concerns structures belonging to the limbic system, across three different developmental stages: “early” (PND 21-25), “middle” or juvenile (PND 28-32) and “late” or adolescent (PND 35-39). The comparison between early and middle juvenile rats data highlights patterns of enhanced connectivity from both Striata to both Hippocampi and from there to Nucleus accumbens (NAcc) and Orbitofrontal Cortex (OFC), along with pathways from right Striatum to NAcc, from OFC to ipsilateral NAcc and vice versa, from left Prefrontal Cortex to ipsilateral OFC and eventually from left Striatum, NAcc and Prefrontal Cortex to contralateral OFC. After only one week, entering into adolescence, the first pathway mentioned above keeps on growing while other patterns appear: both NAcc are reached from contralateral Striatum, right Hippocampus from both Amygdalae and finally left NAcc from right Hippocampus. It’s interesting to notice the fact that, independently from the age when these connections develop, Striata of both hemispheres send axons to both Hippocampi and NAcc sides, both Hippocampi reach left NAcc and OFC and finally both NAcc sides reach right OFC. Namely, the Striatum indirectly reaches the OFC passing through Hippocampus and NAcc. Other data obtained with DTI highlighted how adolescents’ neurite density may be affected within subcortical gray matter, especially for what concern NAcc and OFC at “late” stage (adolescence). Finally, we investigated by 1H-MRS the levels of metabolites in the anterior part of the hippocampus: we put into evidence an increase in myo-inositol during juvenile transition plus a taurine reduction and total choline increase during adolescent transition. In this paper, the aforementioned pattern guides the formulation of hypothesis concerning the correlation between the establishment of new and novel brain connections and the emergence of behavioral traits that are typical of adolescence.